1995
DOI: 10.1128/jcm.33.4.958-961.1995
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ambient temperature on competence of deer ticks as hosts for Lyme disease spirochetes

Abstract: We determined whether the temperature of extrinsic incubation affects the competence of vector ticks as hosts for Lyme disease spirochetes (Borrelia burgdorferi). Larval Ixodes dammini ticks that had engorged on spirochete-infected C3H mice were incubated continuously at various temperatures, and the gut contents of the resulting nymphs were examined for spirochetes by direct immunofluorescence microscopy. Spirochetes were present in virtually all nymphs kept at 27؇C or less for 6 months, in only 10% of those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 33 publications
1
17
1
Order By: Relevance
“…The population dynamics of vector-borne pathogens inside their arthropod vectors are also highly dependent on abiotic factors, such as temperature (Sternberg and Thomas, 2014). For example, warmer temperatures reduce the vectorial capacity of malaria mosquitoes (Paaijmans et al, 2011) and high temperatures can clear the Lyme disease pathogen from ticks so that they are no longer infectious to mice (Shih et al, 1995). Taken together, these observations suggest that temperature (and other abiotic variables) could influence the outcome of the interactions between strains in mixed infections in the arthropod vector, but to date there are no studies on this subject.…”
Section: Introductionmentioning
confidence: 99%
“…The population dynamics of vector-borne pathogens inside their arthropod vectors are also highly dependent on abiotic factors, such as temperature (Sternberg and Thomas, 2014). For example, warmer temperatures reduce the vectorial capacity of malaria mosquitoes (Paaijmans et al, 2011) and high temperatures can clear the Lyme disease pathogen from ticks so that they are no longer infectious to mice (Shih et al, 1995). Taken together, these observations suggest that temperature (and other abiotic variables) could influence the outcome of the interactions between strains in mixed infections in the arthropod vector, but to date there are no studies on this subject.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have shown that the extrinsic incubation temperature (EI) affects survival growth and transmission of lyme disease spirochete, Borrelia burgdorferi, and hence the competence of its ixodid tick vector (Shih et al, 1995 Furthermore, Barbour (1984) found that lyme disease spirochete B. burgdorferi did not grow when cultured in BSK II medium at temperature in excess of 37P o…”
Section: Introductionmentioning
confidence: 99%
“…Relatively few studies examine vector competence across species of ticks feeding on the same hosts (Henning et al 2014). The influence of ambient temperature on vector competence in tick species was not existent for Venezuelan equine encephalomyelitis (Dohm & Linthicum 1993), and temperatures above 27°C were not conducive to vector competence for B. burgdorferi (Shih, Telford & Spielman 1995).…”
Section: E C T O R C O M P E T E N C E ( B )mentioning
confidence: 99%